OCCURRENCE OF GOITER IN TRIBAL POPULATION OF PADERUMANDAL OF VISAKHAPATNAM - SIRINIVASU, PONNADA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The hill tracts of Eastern Ghats in the habitat of tribal communities. The geo-ecological conditions to some extent responsible for their health condition. One of the major health problem in this locality is the goiter. The women at the age of > 25 years are more prone to goiter than the male counter parts.